Moving skills from hands to heads: Import of technology and export performance - Giorgio Barba Navaretti; Marzio Galeotti; Andrea Mattozzi (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper examines the link between imported technologies and a country's export performance, as measured by product quality. The analysis is set in the background of the process of regional integration between the EU and its neighbouring developing countries. The underlying question is whether trade integration fosters or dampens learning and technological upgrading. We find that unit values of exports from these countries to the EU rose steadily between 1988 and 1996, relative to the unit values of world exports to Europe. If increases in unit values satisfactorily proxy increases in product quality, then trade integration has fostered product upgrading and technological learning in the sample countries. We find that imported technologies and other sources of knowledge have a strong bearing on this pattern. Technological inflows are captured by the degree of involvement of European companies in export flows from our sample countries (Outward Processing Trade) and by the skill content of the machines imported. Keywords: Technology imports, export performance, regional integration, textile industry.
Keywords: F1; O1; O3; 330; Technology imports; export performance; regional integration; textile industry; Technologietransfer; EU-Staaten